LncRNA HOXA-AS2 represses endothelium inflammation by regulating the activity of NF-κB signaling - Zhu, Xinxing; Liu, Yanli; Yu, Jinjin; Du, Jiang; Guo, Rui; Feng, Yanyan; Zhong, Genshen; Jiang, Yizhou; Lin, Juntang (Atherosclerosis, 2019)
Endothelium inflammation, which can lead to endothelial activation and dysfunction, is widely accepted as the major event in multiple vascular disorders. The lncRNA HOXA-AS2 was previously reported to be involved in multiple inflammation-linked cancers. However, the role of HOXA-AS2 in endothelium inflammation is poorly understood. This study aims to determine the regulatory role of HOXA-AS2 in endothelium inflammation and related vascular diseases. High throughput mRNA sequencing was performed to establish expression profiles after HOXA-AS2 depletion. We extracted total RNAs of human peripheral blood mononuclear cells from normal control group and experimental group with carotid artery atherosclerosis, and performed qRT-PCR to assay the correlation between HOXA-AS2 expression and inflammatory vascular diseases. Inhibition of HOXA-AS2 can induce the activation of NF-κB signaling and subsequent inflammatory response. More importantly, HOXA-AS2 is inversely found to be inversely regulated by NF-κB in a negative feedback manner by helping recruit BRD4/P-TEFb complex to HOXA-AS2 promoter region, therefore facilitating release of the promoter-proximal paused RNA polymerase II and activating transcription elongation. We identify HOXA-AS2 as a critical repressor of endothelium inflammation. Moreover, this study offers us a new way to balance the NF-κB signaling-driven excessive endothelium inflammation by establishing a NF-κB/HOXA-AS2 negative feedback loop. Based on these findings, we conclude that HOXA-AS2 may serve as a crucial therapeutic target for various vascular disorders which are significantly associated with endothelium inflammation. [Display omitted] •We identify lncRNA HOXA-AS2 as a critical repressor of endothelium inflammation.•HOXA-AS2 has a significant correlation with carotid artery atherosclerosis.•HOXA-AS2 represses the activation of NF-κB signaling by controlling IκBα degradation and RelA acetylation at K310 site.•NF-κB inversely activates the transcription elongation of HOXA-AS2 by establishing a NF-κB/HOXA-AS2 negative feedback loop.